THE MEDIATING ROLE OF INTERACTIVE LEADERSHIP IN THE RELATIONSHIP BETWEEN ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND BURNOUT IN EMPLOYEES (Third Sector Social Economic Review, 2023)
The aim of the study is to determine the mediator role of interactional leadership behavior in the effect of organizational citizenship behavior of employees on burnout in organizations. Organizational citizenship behavior and the perception of burnout form relationally opposing behaviors. While organizational citizenship behavior, which is expressed as “over-role behaviors”, is an organizational behavior that is evaluated positively, the perception of burnout is a negative behavior that occurs emotionally, mentally and physically. There are studies conducted on different sample groups between these two variables. However, determining the mediator role of transactional leadership makes this study unique. Within the scope of the research, the research model and hypotheses were formed by using the relational survey method, one of the quantitative research methods. In this direction, data were obtained from 392 employees working in institutions/businesses operating in the service sector in the province of Ankara, through the questionnaire form. The obtained data were analyzed using SPSS package program. In line with these analyzes, it was concluded that there is a negative relationship and effect between organizational citizenship behavior and burnout. In addition, it has been determined that transactional leadership behavior has a mediating role.
Keywords: Citizen; Organizational Citizenship Behavior; Burnout; Leadership; Transactional Leadership